Intercomparing the Response of Tropospheric and Stratospheric Temperature to Two Types of El Niño Onset - Shujie Chang; Min Shao; Chunhua Shi; Hua Xu (Advances in Meteorology)
Based on Remote Sensing Systems-retrieved temperature data in the period of January 1979 to February 2016, the response of stratospheric and tropospheric temperature in boreal winter to two previously defined types of El Niño [spring (SP) and summer (SU)] is investigated. The results show that, the response of temperature under SP onset involves a significant positive anomaly, with a symmetric distribution about the equator over the Indian Ocean region in the lower troposphere (850 hPa) and a negative anomaly in the lower stratosphere (50 hPa). Meanwhile, in the area 30°N and 30°S of the equator, most parts of the lower stratosphere feature a positive anomaly. This indicates that SP El Niño events are more conducive than SU events to warming the lower stratosphere. The atmospheric circulation structure over the tropical Indian Ocean is beneficial to the upward transfer of warm air to the upper layer. In contrast, the structure over the tropical Pacific Ocean favors the warming of upper air. On the other hand, the Eliassen–Palm (EP) flux is small and the heat flux is negative during SP-type events. Thus, the EP flux and Brewer–Dobson circulation decrease, making the temperature higher in the upper troposphere-lower stratosphere region at low latitudes.